Perbandingan Peran Kader Posyandu dalam Mengedukasi Pemenuhan Kebutuhan Gizi Balita di Daerah dengan Stunting Tinggi dan Rendah - Lu'lu' Washilatul Ulfah; Nunung Siti Sukaesih; Ria Inriyana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Stunting is a serious nutritional problem that affects the nation's productivity. Apart from being caused by toddlers' inadequate nutritional intake, inadequate family education also causes stunting’s increases. Family education about a toddler’s nutritional intake is not only the mother's responsibility, but there is a posyandu cadre’s role as the closest group to conveying information. This study aims to determine the differences between posyandu cadre’s role in educating about toddler nutritional needs at high and low stunting areas. It’s located in Sumedang as West Java highest stunting area, specifically in Margamukti as a low and Mulyasari Village as a high stunting area. This comparative study is quantitative research used a cross-sectional design and total sampling technique with 70 respondents which divide into 35 respondents in low stunting area and 35 respondents in high stunting area. The sample criteria were posyandu cadres who registered at the village office. Data was collected by paper and analyzed by Mann Whitney test. The results show that there is significant difference in the frequency and method of educational activity with p-value 0,001 and 0,008 < a = 0,05, so there are no other differences were found that could indicate a comparison of cadres role at high and low stunting areas. Researchers recommend the educational frequency and method at low stunting areas can be adopted at high stunting areas.